Intradialytic Exercise: One Size Doesn’t Fit All - Valenzuela, Pedro L.; de Alba, Ana; Pedrero-Chamizo, Raquel; Morales, Javier S.; Cobo, Fernando; Botella, Ana; González-Gross, Marcela; Pérez, Margarita; Lucia, Alejandro; Marín-López, M. T. (Frontiers in Physiology, 2018)
Purpose: Hemodialysis patients commonly have impaired physical performance and mental health. We studied the effects of an intradialytic exercise program on these variables. Methods: 27 patients (33% women; 68±13 years) were enrolled in a 14-week intradialytic endurance-resistance training program (‘exercise’ group, 40 programmed sessions per patient); 40 hemodialysis patients (28% women; 68±11 years) performing no exercise during the same time length were used as controls. Endpoints included physical performance (6-minute walk test [6MWT], 10-repetition sit to stand [STS-10] and handgrip strength), emotional status (Beck’s depression inventory and State-Trait Anxiety Inventory), and mental and physical component scores of the short-from (SF)-12 Health Survey. Results: There were no differences (p>0.05) between groups at baseline for sex distribution, or mean age, body mass index and time spent on dialysis. Exercise benefits were observed for 6MWT (11 and -3% for the exercise and control groups, respectively; p<0.001), STS-10 performance time (-22 and 6%; p<0.001) and handgrip strength (4 and -4%; p<0.02). No significant benefits (p>0.05) were observed for emotional status endpoints or SF-12 component scores. Despite significant benefits on physical performance, the proportion of clinically meaningful responders was low (<50%). Responsiveness was dependent on baseline physical performance (p<0.05) but not on age or sex (p>0.05). Conclusion: A 14-week intradialytic training program induced significant improvements on physical performance. However, the rate of clinically meaningful responders observed in the present study was low, being the level of responsiveness dependent on baseline physical status. Efforts to individualize exercise prescription are needed in clinical practice.